Wiedza organizacji w sieci a wiedza sieci - podejście systemowe - Maj, Ireneusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main asset of network organizations is knowledge whereas relations with other organizations become the basis of adaptation under circumstances when change, chaos and long-term future unpredictability are permanent and natural. It is obvious that relations between organizations have to influence the knowledge conversion both in organizations themselves as well as between related organizations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 172-182